MNT and Emerging Concepts of MNT-MYC Antagonism - Yang, Guang (Genes (Basel), 2017)
MYC family proteins play fundamental roles in stem and progenitor cell homeostasis, morphogenesis and cancer. As expected for proteins that profoundly affect the fate of cells, the activities of MYC are regulated at a multitude of levels. One mechanism with the potential to broadly affect the activities of MYC is transcriptional antagonism by a group of MYC-related transcriptional repressors. From this group, the protein MNT has emerged as having perhaps the most far-reaching impact on MYC activities. In this review, we discuss the current understanding of MNT, its regulation and how, as a MYC antagonist, it functions both as a tumor suppressor and facilitator of MYC-driven proliferation and oncogenesis.